The Anemone, The Porcupine: Hairy Cell Leukaemia - Bajaj, Anubha (Journal of Clinical and Diagnostic Pathology, 2018)
Theobjective of reviewing Hairy Cell Leukaemia may be achieved by emphasising the condition as a category of chronic lymphocytic leukaemia with hair like protrusions of the cytoplasm situated on the aberrant B cell surface. An infrequent disorder, hairy cell leukaemia contributes an estimated 2% of lymphoid malignancies with a male predominance ( M:F ::4-5:1). A majority (90%) of instances depict a mutant immunoglobulin heavy chain variable region (IGHV). The haematopoietic stem cells (HSCs) elucidate a B raf proto-oncogene( BRAF V600E gene- 7q34). An enlarged spleen may be discerned along with pancytopenia as a presenting symptom. The morphology of specific hairy cell leukaemia may be on account of an in vitro interaction of primary hairy cells with BRAF genes and MEK inhibitors, which incite a prominent MEK - ERK dephosphorylation, thereby curtailing transcriptional outpourings of the RAS- RAF- MEK-ERK pathway. Bone marrow aspiration or bone marrow trephine biopsy may be inadequate for diagnosis in 30%-50% individuals on account of extensive fibrosis and the bone marrow sections depict a characteristic interstitial infiltration of leukaemia cells.. Reticulin stains exhibit broad, dense reticulum fibres surrounding the individual or aggregates of leukaemia cells with fibrotic extensions into the abutting bone marrow. The immune reactivity of classic hairy cell leukaemia is concurrent CD19+ CD20+,CD 11c+, CD25+, CD103+ and CD123+. Immune staining for CD20+, annexin 1 and VE1 (a BRAF V600E stain) validates the diagnosis and analyses the extent of malignant bone marrow infiltration. Application of inhibitors of BRAF V600E gene is efficacious in patients resistant to standard therapy. An enlarged spleen beyond 3 centimetres of the left costal margin, a white blood cell count greater than 10000 cells/µL , circulating hairy cells in the peripheral blood greater than 5000 cells/µL and a β 2 micro-globulin level exceeding twice the normal range of 3 µg/ml delineate an inferior outcome with resistance to purine analogues (PNAs). CD38+ elucidation ensures a worse prognosis as does the lack of an IGHV mutation with a reduced overall survival,. A lack of BRAF genetic mutation in 10% -20% of hairy cell leukaemia comprises of inferior prognosis.
Keywords: Hairy Cell Leukaemia; Chronic Lymphocytic Leukaemia; BRAF; Pancytopenia; IGHV